Locating in University-Related Technology Parks: An Exploratory Study - Gutierrez, Ben Paul B. (Philippine Management Review; Vol 9 (2001), 2016)
This research explores the factors important in the choice of a technology park location.  After drawing out potential factors from the literature and from local experts, a questionnaire was designed and fielded among local prospective investors to the park.  Results reveal that local information technology organizations place more value to economic considerations rather than university-related locator-factors.  The paper ends with the implications of the study for the conceptualization of the University of the Philippines Diliman Science and Technology Park.